Aggregation of Aqueous Kaolin Suspensions in the Presence of Cationic Polyelectrolytes, Anionic Polyelectrolytes and their Mixtures - Zh. A. Lakhbayeva; R. S. Taubayeva; S. M. Tazhibayeva; A. A. Barany; K. B. Musabekov (Eurasian Chemico-Technological Journal, 2016)
The influence of anionic, cationic synthetic polyelectrolytes and their mixtures on the aggregation of kaolin hydrosuspension has been studied by means of spectrophotometry, electrophoresis and dynamic light scattering (DLS). An enhancement of the flocculating property of the cationic polyelectrolyte FO 4650 in accordance with its consumption increases from 0.77 mg/g to 7.7 mg/g has been found. At these conditions the relative size of floccules (R) increases from 1.0 to 13.0. The increase of the flocculating property accordingly to the increasing charge of anionic polyelectrolyte is observed in mixtures of cationic and anionic polyelectrolytes. The time dependences of R in presence of the weakly charged cationic polyelectrolyte mixtures reach a plateau region. This can be associated with the formation of electrostatic contacts between the solid surface and the polymer mixtures, as well as with stabilizing equilibrium conformation of macromolecules. It has been found that mixtures of oppositely charged polyelectrolytes lead to more efficient aggregation of particles than individual polyelectrolytes. This process is enhanced by the introduction primarily of the cationic polyelectrolyte and then the anionic one (R = 6‒10). Use of the preformulated mixtures of polymers leads to the marked increase in degree of particle aggregation (R = 12). The reason is an interaction of kaolin particles with inter-polymer complex formed by electrostatic attraction of oppositely charged polyelectrolytes.